'Bac' to the future: bioengineering lantibiotics for designer purposes. (21st November 2012) - Molloy, Evelyn M.; Ross, R. Paul; Hill, Colin
Abstract : Bacteriocins are bacterially produced peptides or proteins that inhibit the growth of other bacterial strains. They can have a broad (effective against multiple genera) or narrow (effective against specific species) spectrum of activity. The diversity of bacteriocins found in Nature, in terms of both spectrum of activity and physiochemical properties, offers the possibility of multiple applications in the food and pharmaceutical industries. However, traditional screening strategies may not provide a sufficient range of natural molecules with specifically desired properties. Research suggests that bioengineering of existing inhibitors has the potential to address this issue, extending the application of natural bacteriocins for use in novel settings and against different targets. In the present paper, we discuss the successful implementation of bioengineering strategies to alter and even improve the functional characteristics of a bacteriocin, using the prototypical lantibiotic nisin as an example. Additionally, we describe the recent use of the nisin-modification machinery in vivo to enhance the properties of medically significant peptides.